STUDY PERANCANGAN DINDING PENAHAN LONGSORAN PADA RUAS JALAN POROS KM.38 SEMOI/SEPAKU KABUPATEN KUTAI KARTANEGARA - SAPUTRO, DEVI YANTO (KURVA S JURNAL MAHASISWA, 2017)
East Kalimantan is a mountainous area, therefore the construction of roads is also onaverage in the top of the mountain, because the function of the road is very important for theneeds of the community and is a liaison between provinces where many roads are not feasibledue to landslides on the side of the road and it is a way axis. the authors make this final task bymaking a landslide handling research in the form of retaining wall in km.38 semoi / sepaku andused two types of retaining wall of the cantilever wall and counterfort and addition of pile.From the above problems and objectives, problem limitation is required by calculating thestability and control of the retaining wall with the coulomb and rankine methods, calculatingthe carrying capacity control with the converse labbare method, and not calculating the costbudget plan.In this final project the authors also make intent and objective is to evaluate thestability of the soil before and after the occurrence of avalanches on the road km.38 semoi /sepaku and then do the recalculation with the stability of shifting and rolling so that it can be asecurity factor on the calculation and the purpose of preparation of the final task is to be able toplan the dimensions of the retaining wall that is safe and economical on cantilever type walland counterfort wall. Data retrieval method used in this thesis research with primary methodthat is sondir, boring, as well as measurement of topography and secondary method in the formof literature study, work drawing. After the material in need fulfilled then done the analysis ofthe calculation by making the retaining wall design and in this final task the authors comparetwo types of cantilever and counterfort with rankine and coulomb method and on the carryingcapacity by converse labbare method.rom result of analysis got stability factor to bolsters on cantilever wall with coulombmethod equal to 2,61 ≥ 2, rankine method 2,4 ≥ 2, and got factor of shear stability with coulombmethod equal to 0,356> 2, rankine method 0,324> 2 and stability of collapse on the coulombmethod of 1.935> 3 and rankine 2.302> 3. On the wall counterfort can be stability valuebolsters with coulomb method of 2.3 ≥ 2, rankine method 2.1 ≥ 2, and the shear stability factorobtained by the method of coulomb of 0.381> 2, Rankine method 0.347> 2 and the stability of2collapse on the coulomb method of 1.34> 3 and rankine 1.24> 3. Also obtained security controlof the bearing capacity of piles on the cantilever wall of individuals of 2.73> 3.6 and pilesgroups of 5.451> 3.6 while on individual counterfort walls of 2.52> 3.6 and group piles of7.57> 3.6.The conclusion of the final project that the authors make is of cantilever typecantilevered wall with coulomb method obtained safe stability of bolsters style, unsafe shearforce stability, and collapse also in unsafe condition, with rankine method obtained value on thestability of bolsters safe, stylish stability insecure shear and collapse in can be insecure value.While on counterfortfort retaining wall type with coulomb method obtained safe stability ofguling style, unsafe shear stress stability and collapse also obtained unsafe condition, and onrankine stability method of bolsters in can safe value, unsafe stability of shear force, andstability of collapse not secure. Therefore in need of pile bearing capacity as a vertical loadcontainer that works.